The Quality of Yoghurt Fortification Tuna Fishbone (Thunnus sp.) Nanocalcium: Physicochemistry and Microstructure - Shodiq, Berliana; Lailasari, Umi; Prasetiyo, Dimas Teguh; Pambudi, Ridho; Nurdin, Muhammad Alfan (Faculty of Animal Science Universitas Brawijaya, 2024)
Calcium is very important mineral for human body. Fortification of natural calcium source into yoghurt can be a way to provide calcium requirement. Fortification nanocalcium into yoghurt also can increase bioavailability of calcium. This research aimed to determine the effect of tuna fishbone nanocalcium fortification on total acidity, pH, water holding capacity, viscosity, syneresis, firmness, cohesiveness, particle size and particle distribution of yoghurt. The treatment used were 100 ml yoghurt + 0% nanocalcium (P0), 100 ml yoghurt + 0.12% nanocalcium (P1), 100 ml yoghurt + 0.24% nanocalcium (P2), and 100 ml yoghurt + 0.48% nanocalcium (P3). This research carried out 4 treatments and 3 repetitions. The results showed that the fortification had a significant effect (p < 0.05) on yoghurt's total acidity, pH, water holding capacity. The result of viscosity, firmness and cohesiveness showed the highly significant effect (p < 0.01) in yoghurt and the rest variable result like particle distribution, particle size and syneresis of yoghurt fortification showed no significant effect (p > 0.05). The average result P0; P1; P2; P3 of total acidity () was 1.395±0.085; 1.343±0.0471; 1.272±0.0364; 1.242±0.0469, pH was 4.38 ± 0.04; 4.39 ± 0.01; 4.40 ± 0.03; 4.45 ± 0.01, water holding capacity (%) was 71.17 ±1.90; 71.77±1.96; 74.56 ± 2.2, viscosity (%) was 84.473 ± 0.537; 90.317 ± 0.585; 92.873 ± 1.175; 95.073 ± 0.616, syneresis (%) was 28.140±6.97; 28.790 ±2,19; 27.253 ±4.72; 27.890 ± 4.04, firmness was 42.443 ± 1.093; 45.627 ± 0.994; 47.370 ± 1.295; 54.290 ± 2.509, cohesiveness was 12.679±0.244; -13.180±0.340; -13.913±0.270; -14.492±0.169, particle size (µm) was 9.820±1.950; 8.797±0.120; 8.470±1.869; 8.303±2.442, and particle distribution was 3.027 ±0.01; 2.781 ±0.16; 2.714 ±0.313; and 2.578 ±0.22. The conclusion of this research was fortification of tuna fishbone nanocalcium had effect to decrease total acidity, syneresis, cohesiveness, particle size and particle distribution of yoghurt. Also, the fortification can increase pH, water holding capacity, viscosity and firmness of yoghurt.